Polygenic Risk Score Improves Melanoma Risk Assessment in a Patient Cohort from the Veneto Region of Italy - Stefania Pellegrini; Thomas P. Potjer; Paola Del Bianco; Antonella Vecchiato; Alessio Fabozzi; Luisa Piccin; Debora Tonello; Nienke van der Stoep; Emily Tinsley; Maria Teresa Landi; Mark M. Iles; Chiara Menin (Biology)
Recent genome-wide association studies (GWASs) have identified many single nucleotide polymorphisms (SNPs) that alone weakly affect melanoma risk, but their combined effect on a polygenic risk score (PRS) can have a far bigger impact on estimating risk. However, the PRS is not yet at the stage of being utilized in clinical practice, and further evidence is needed. In this study, 270 melanoma patients fulfilling the criteria for a suspected genetic predisposition but with a negative genetic test for high/medium-penetrance genes were genotyped for 57 SNPs selected in previous GWASs to construct a PRS model. We found a significantly higher mean PRS57 in all melanoma cases than in controls (0.58 vs. 0.00, p < 0.001), and the mean PRS57 in multiple primary melanoma cases was twice that in single melanoma cases (0.689 vs. 0.362, p = 0.025). Interestingly, our results confirm the association of the PRS57 not only with other melanoma risk factors but also with a younger age at diagnosis. This evidence supports the potentially powerful discriminative role of PRS in the selection of high-risk patients who should undergo stricter surveillance protocols.